2012
DOI: 10.1002/anie.201201605
|View full text |Cite
|
Sign up to set email alerts
|

Chemo‐ and Regioselective Direct Hydroxylation of Arenes with Hydrogen Peroxide Catalyzed by a Divanadium‐Substituted Phosphotungstate

Abstract: Peroxide in, phenol out: The catalyst [γ-PW(10)O(38)V(2)(μ-OH)(2)](3-) showed high activity in the hydroxylation of various aromatic compounds with aqueous H(2)O(2). The system was regioselective, producing para-phenols from monosubstituted benzene derivatives. Furthermore, alkylarenes with reactive side-chain C sp 3-H bonds could be chemoselectively hydroxylated without significant formation of side-chain oxygenated products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
60
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(65 citation statements)
references
References 46 publications
5
60
0
Order By: Relevance
“…The reaction smoothly proceeded in acetonitrile and its mixtures with t-BuOH, but in contrast to the oxidation of alkyl-and methoxybenzenes [143], the presence of acid co-catalyst was not crucial.…”
Section: Vanadiummentioning
confidence: 98%
“…The reaction smoothly proceeded in acetonitrile and its mixtures with t-BuOH, but in contrast to the oxidation of alkyl-and methoxybenzenes [143], the presence of acid co-catalyst was not crucial.…”
Section: Vanadiummentioning
confidence: 98%
“…Different early transition metals substituted POMs showed different activities in the synthesis of phenol from benzene [17]. Among them, vanadiumsubstituted POMs (for example, PMoV) showed good performance in the hydroxylation of benzene to phenol and aroused many studies [9][10][11][12][13][14][15][16][17]. Multi vanadium have been introduced into POMs in order to improve their catalytic activities, but the yields of phenol achieved by the three catalysts were decreased as follows: H 4 There is a strategy to increase the vanadium content simultaneously avoiding vanadium accumulation in POMs anions: using vanadium-containing cations instead of their usual counter ions (H + , Na + , K + ).…”
Section: Introductionmentioning
confidence: 99%
“…Their catalytic activities can be finely manipulated because various early transition metals can be introduced into their structures at molecular levels [9][10][11][12][13][14][15][16][17][18][19][20][21]. Different early transition metals substituted POMs showed different activities in the synthesis of phenol from benzene [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the hydroxylation reaction was examined with benzene-d 6 , there was no KIE (k H /k D ¼ 1.0) observed (Table 2, entries 1 and 8), which indicated that C-H activation in the benzene ring was not the rate-determining step. 41 Therefore, the activation of molecular oxygen may be the rate-determining step.…”
mentioning
confidence: 99%